Healthcare Waste: An Overview from Generation to Disposal - Shikoh Naz; Syed Muhammad Zulfiqar Hyder Naqvi; Saima Asim (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Madam, waste resulting from healthcare activities consists of a diversity of substances like used syringes, soiled dressings, diagnostic samples, biochemical substances, pharmaceutical products, medical devices, radioactive materials, and body parts1